2019
DOI: 10.18662/po/71
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Consent Silence in Cyberbullying

Abstract: Weather the silence of bystanders is consent or not in cyberbullying type incidents has risen a scientifically debate in the field of victim-aggressor-witness dynamics research. Silence implies consent represents a concept of social interaction, which generally states that people tend to assume lack of a response or opinion to an action as a tacit approval of that action. Our research team has developed the project Keeping youth safe from Cyberbullying, aiming to deeper understand the dynamics of different cyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Further findings indicated that the bullied students are often avoided disclosing their experiences due to the feelings of embarrassment and weakness, being concerned with not worrying their parents, and fear of being deprived of communication (20). In a study by Rad on Romanian adolescents, the main predictor of continued cyberbullying was silence in response to the bully's behaviors (21). Moreover, female gender and education in the secondary high school significantly increased the likelihood of experiencing harassment (P < 0.001).…”
Section: Discussionmentioning
confidence: 98%
“…Further findings indicated that the bullied students are often avoided disclosing their experiences due to the feelings of embarrassment and weakness, being concerned with not worrying their parents, and fear of being deprived of communication (20). In a study by Rad on Romanian adolescents, the main predictor of continued cyberbullying was silence in response to the bully's behaviors (21). Moreover, female gender and education in the secondary high school significantly increased the likelihood of experiencing harassment (P < 0.001).…”
Section: Discussionmentioning
confidence: 98%
“…The data that were obtained were compared in physical training courses that included music and those that did not include music, as well as the three secessions of the warming up fitness part and warming down phase [28]. The independent variable in this study was believed to be the music, and the dependent variable was the step count obtained using pedometric analysis [29]. A T-test is carried out in order to identify the significant difference, and an ANOVA repeated measures test is carried out in order to ascertain whether or not a disparity exists between the populations being compared [30].…”
Section: Analysis Of Datamentioning
confidence: 99%
“…It promotes hate speech normalization, with victims and bystanders adopting a passive mentality, not involving or acting. In this context, an important observation was raised by one group of researchers regarding bystanders not taking action because they feel strongly related to the target of hate speech (Bellmore et al, 2012;Barchia & Bussey, 2011), alluding to the influence empathy may play in affect (Rad et al, 2019).…”
Section: Digital Correlatesmentioning
confidence: 99%